Effect of Nitrogen on the Amorphous Structure and Subthreshold Electrical Conduction of GeSeSb‐Based Ovonic Threshold Switching Thin Films. Issue 5 (26th November 2019) - Verdy, Anthonin; d'Acapito, Francesco; Dory, Jean-Baptiste; Navarro, Gabriele; Bernard, Mathieu; Noé, Pierre
Abstract : Herein, the amorphous structure of Ge–Se–Sb–N chalcogenide thin films is investigated through Raman, infrared, and X‐ray absorption spectroscopies in the light of the electrical performances of such materials once integrated in ovonic threshold switching (OTS) selector devices. In particular, it is shown that the presence of homopolar and wrong bonds in the amorphous structure has a detrimental impact on the subthreshold leakage current of the OTS devices. Although the presence of Sb–Sb and Ge–Sb bonds tends to increase the leakage current in pristine devices, the presence of Se–Se bonds is correlated to a significant device‐to‐device dispersion of subthreshold characteristics after the device initialization. Finally, the incorporation of a proper N concentration in Ge–Se–Sb glass permits to suppress the homopolar bonds, leading to a very low leakage current and a low device‐to‐device dispersion. Abstract : The critical role of homopolar and wrong bonds in amorphous Ge–Se–Sb–N films on the performance of ovonic threshold switching (OTS) selector devices is investigated. Using a proper concentration of N is shown to be a key engineering tool of the amorphous structure allowing to remove such detrimental bonds and thus achieving reliable OTS materials.